Serum deprivation alters lipid profile in HN9.10e embryonic hippocampal cells. (4th March 2015) - Garcia-Gil, Mercedes; Lazzarini, Andrea; Lazzarini, Remo; Floridi, Emanuela; Cataldi, Samuela; Floridi, Alessandro; Albi, Elisabetta
Highlights: Serum deprivation increases Ceramide 16:0 in embryonic hippocampal cells. Serum deprivation decreases cholesterol in embryonic hippocampal cells. Serum deprivation increases sphingosine-1- phosphate in embryonic hippocampal cells. Abstract: The understanding of the mechanism of apoptosis is important to improve the use of stem cells for the treatment of neurodegenerative disorders. Sphingolipids are bioactive molecules involved in the regulation of cell fate. In HN9.10e embryonic hippocampal cells, serum deprivation induces apoptosis preceded by sphingomyelinase activation and raise of ceramide levels. Increasing evidence indicates that individual ceramide species regulated by specific pathways in distinct subcellular compartments might carry out distinct cellular functions, but the ceramides species involved in embryonic hippocampal cell death induced by growth factor deprivation are unknown. In the present paper, by using the UFLC–MS/MS methodology, we have investigated the effect of serum deprivation on the lipid profile in HN9.10e cells. At 48 h of serum deprivation, we detected a decrease in cholesterol and increase in sphingosine-1-phoshate 18:1, phosphatidylcholine 18:1 18:0, sphingomyelin 18:1 16:0 and in ceramides 18:1 16:0; we also found an increase in saturated/unsaturated fatty acid ratio in sphingomyelin. We hypothesize that the rearrangement of sphingo- and glycerolipids with increase of saturated fatty acids in serum-deprivated, neural cells might represent a cellular response aimed at holding cholesterol inside the cells.